Clinical profile and predictors of immediate outcome in children with status epilepticus - P. Nandini, Nitish Kumar; Shenoy, K. Varadaraj (International Journal of Contemporary Pediatrics, 2025)
Background: Aim of the study was to study the clinical profile, and predictors of immediate outcome in children aged 1 month to 15 years, with status epilepticus admitted to tertiary care center. Methods: A prospective study of 43 patients admitted in department of pediatrics in Father Muller medical college between October 2017 to April 2019. They were evaluated for their clinical presentation, treatment profile and immediate outcome. Results: Twenty-one children (49%) were between 1 to 5 years, seven children (16%) were below 1 year and fifteen (35%) were between 5 to 15 years. Thirty children (70%) were male and thirteen (30%) were female. Twenty-six patients (60.4%) had unprovoked status epilepticus. Twelve children (28%) had pre-existing neurological abnormality. Three patients died (6%) during hospital course and six patients (13.9%) had new onset neurological deficits and rest recovered. Conclusions: Unprovoked seizures, presence of pre-existing neurological abnormalities, significant birth history, metabolic abnormalities and need for ventilation was associated with new onset neurological deficit and mortality. Overall children with preexisting neurological abnormality presenting with status epilepticus have poorer outcome.